Characterisation of fused deposition modeling 3D printers for pharmaceutical and medical applications. (26th November 2018) - Feuerbach, Tim; Kock, Stefanie; Thommes, Markus
Abstract: Fused deposition modeling (FDM) is a promising 3D printing technique for the fabrication of personalized drug dosage forms and patient-specific implants. However, there are no market products produced by FDM available at this time. One of the reasons is the lack of a consistent and harmonized approval procedure. In this study, three FDM printers have been characterised with respect to printing parameters relevant for pharmaceutical and medical applications, namely the positioning, hot-end temperature, material residence time, printing velocity and volumetric material flow. The printers are the Ultimaker 2 (UM2), the PRotos v3 (PR3) as well as an in-house developed printer (IDP). The positioning results showed discrepancies between the printers, which are mainly based on different types of drive systems. Due to comparable utilised hot-ends and nozzle geometries, the results for the temperature and residence time distribution measurements were quite similar. The IDP has a high positioning accuracy but is limited with respect to printing velocity, while the achievable material volume flows were different for all printers. The presented characterisation method aims to contribute to the development of a harmonized equipment qualification framework for FDM printers, which could lead to an acceleration and facilitation of an approval procedure for 3D printed products.